Cumplimiento de la inversión en el sector agrícola en relación con el sistema general de participaciones -SGP-: caso municipio de Fusagasugá- Cundinamarca- Colombia (2019)
The management of public resources demands the commitment in the establishment of controls, making the optimization possible in the destination that the expenditure and the social investment in the municipalities should have. In this sense and taking into account the coresponsibility that assists the territorial entities, in relation to the transfers far their specific destination and general purpose, punctually with the General System of Participations, it is necessary to identify which has been the behavior in the territorial budgetary execution within the agricultural sector; taking into account sorne of the variables that have a direct impact on rural investment. In this regard, it is clear that during the last 10 years the GSP far the countryside has been scarce and this can be supported by the low growth it has had, without exceeding 0.5%, with a low participation in GDP, aspects that distance it from being considered a locomotive of development. The theoretical reference addresses budget autonomy and fiscal decentralization based on the postulates of Bonet, Pérez and Aya la (2014); Maldonado (2011); Daughters and Harper (2006), CEPAL (2009), Cárdenas Salinas,J and Monroy Olmos, H. (2016) among others. Applies to a methodology with exploratory cut based on the documentary contrast supported in academic institutional sources and of the State.